Transcriptional Response of Mycobacterium tuberculosis to Cigarette Smoke Condensate - Willemse, Danicke; Moodley, Chivonne; Mehra, Smriti; Kaushal, Deepak (Frontiers in Microbiology, 2021)
Smoking is known to be an added risk factor for tuberculosis (TB), with nearly a quarter of the TB cases attributed to cigarette smokers in the 22 countries with the highest TB burden. Many studies have indicated a link between risk of active TB and cigarette smoke. Smoking is also known to significantly decrease TB cure and treatment completion rate and increase mortality rates. Cigarette smoke contains thousands of volatile compounds including carcinogens, toxins, reactive solids, and oxidants in both particulate and gaseous phase. Yet, to date, limited studies have analyzed the impact of cigarette smoke components on Mycobacterium tuberculosis (Mtb), the causative agent of TB. Here we report the impact of cigarette smoke condensate (CSC) on survival, mutation frequency, and gene expression of Mtb in vitro. We show that exposure of virulent Mtb to cigarette smoke increases the mutation frequency of the pathogen and strongly induces the expression of the regulon controlled by SigH—a global transcriptional regulator of oxidative stress. SigH has previously been shown to be required for Mtb to respond to oxidative stress, survival, and granuloma formation in vivo. A high-SigH expression phenotype is known to be associated with greater virulence of Mtb. In patients with pulmonary TB who smoke, these changes may therefore play an important, yet unexplored, role in the treatment efficacy by potentially enhancing the virulence of tubercle bacilli.